Sustainable agribusiness in Brazil: leveraging Environmental Education to empower local Producers - Freitas, Mirlaine Rotoly de; Almeida, Wildney Alves de; Ávila, Carla Luiza da Silva (Revista Brasileira de Educação Ambiental (RevBEA), 2025)
This study investigates small-scale agro-livestock producers’ perceptions of integrated agro-livestock systems (IALS) in Mato Grosso do Sul, Brazil, and their alignment with SDGs 2, 4, 12, and 15. Using a tailored questionnaire and socio-environmental analysis, the research reveals that although IALS offer clear economic and environmental benefits, adoption remains limited due to financial constraints and lack of information. The findings underscore the vital role of targeted environmental education and strategic institutional support in promoting sustainable practices such as crop-livestock integration and silvopasture, which can enhance both productivity and ecological resilience.